Efficacy of rivaroxaban compared to standard of care in preventing ischemic stroke in adults with coronary or peripheral vascular disease: an integrated analysis using patient-level data. (25th November 2020) - Barnathan, E.S; Deng, H; Sun, X; Dong, X; La Police, D; Suh, E; Yuan, Z; Berlin, J.A
Abstract: Background: Ischemic stroke is a leading cause of morbidity and mortality. Rivaroxaban has been evaluated in multiple studies of patients with coronary artery disease and/or peripheral artery disease (CAD/PAD) in which ischemic stroke was assessed. Purpose: To determine the efficacy of rivaroxaban compared with standard of care (SOC) in reducing ischemic stroke in adults with CAD/PAD. Methods: Randomized, active- or placebo-controlled Phase 2 or 3 studies evaluating rivaroxaban (2.5 mg twice daily) in adults with CAD/PAD in which ischemic stroke was collected as an efficacy endpoint were included using patient-level data. All stroke was also evaluated as a secondary outcome. ISTH major bleeding (MB) was assessed on treatment + 2 days. Hazard ratios (HR) and p-values for the treatment effect were estimated using Cox proportional hazards models and log-rank tests, respectively, with study as the stratification factor. Mixed effect Cox models (frailty models) were used with treatment as the fixed effect and study as the random effect. Cumulative risk of time-to-first event was assessed using the Kaplan-Meier method. Results: Six studies were included: ATLAS-1, ATLAS-2, COMPASS, COMMANDER HF, GEMINI ACS1 and PIONEER AF-PCI (n=38, 283). Compared with SOC, rivaroxaban significantly reduced the risk of ischemic stroke (HR, 0.63, 95% CI, 0.52–0.77, P<0.001) and all stroke (HR, 0.71, 95% CI, 0.59–0.84, P<0.001), without significant heterogeneity. The frailty model results were consistent. The risk of MB was significantly higher with rivaroxaban compared with SOC (HR, 1.58, 95% CI, 1.37–1.83, P<0.001). Conclusion: Rivaroxaban (2.5 mg twice daily) significantly reduced ischemic stroke and all stroke compared with SOC in patients with acute or chronic CAD/PAD while increasing MB. Funding Acknowledgement: Type of funding source: Private company. Main funding source(s): Janssen Research and Development